2007
DOI: 10.1007/s11104-007-9525-9
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting effects of resource availability and plant mortality on plant community invasion by Bromus tectorum L.

Abstract: The positive effect of disturbance on plant community invasibility is one of the more consistent results in invasion ecology. It is generally attributed to a coincident increase in available resources (due to the disturbance) that allows non-resident plant species to establish (Davis MA, Grime JP Thompson K, J Ecol 88:528-534, 2000). However, most research addressing this issue has been in artificial or highly modified plant communities. Our goal in this study was to investigate the interactive effects of res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 50 publications
1
29
0
Order By: Relevance
“…Evidence for a similar mechanism operating in this study included lower tissue nitrogen concentrations for the 1st and 2nd growth cycles for B. tectorum in competition, relative to B. tectorum grown without competition (Table 5) and the increase in absolute growth and tissue nitrogen concentrations of B. tectorum in competition after fertilizer addition. Bromus tectorum is a nitophile, and its growth and competitive ability is increased as nitrogen availability is elevated [21,44,45] and lowered resource availability has been suggested as to why some plant communities are resistant to B. tectorum invasion [15]. It is by no means clear, however, that lowered soil nitrogen availability can by itself completely assure that B. tectorum cannot invade particular sites [43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence for a similar mechanism operating in this study included lower tissue nitrogen concentrations for the 1st and 2nd growth cycles for B. tectorum in competition, relative to B. tectorum grown without competition (Table 5) and the increase in absolute growth and tissue nitrogen concentrations of B. tectorum in competition after fertilizer addition. Bromus tectorum is a nitophile, and its growth and competitive ability is increased as nitrogen availability is elevated [21,44,45] and lowered resource availability has been suggested as to why some plant communities are resistant to B. tectorum invasion [15]. It is by no means clear, however, that lowered soil nitrogen availability can by itself completely assure that B. tectorum cannot invade particular sites [43].…”
Section: Discussionmentioning
confidence: 99%
“…In the case of B. tectorum, empirical evidence implicates soil resource availability, particularly nitrogen and phosphorus, as an important candidate mechanism [16,17,21,22]. Addition of nitrogen fertilizer greatly increases the growth and competitive stature of B. tectorum [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Inorganic N was higher under B. tectorum than native plants, especially after senescence. As inorganic N levels increase, B. tectorum becomes a better competitor against native species such as Bouteloua gracilis (Lowe et al 2003) and elevated mineral N has been found to increase the success of B. tectorum if other resources are not limiting (Paschke et al 2000, Adair et al 2008. In this way, B. tectorum could facilitate its own spread and domination of plant communities.…”
Section: Discussionmentioning
confidence: 99%
“…Research shows that a fall or winter-timed burn, conducted when most desirable species are dormant, can provide short-term downy brome control by killing 2 seedlings before they produce seed (Brooks 2002;DiTomaso et al 2006). Decreased seedling survival has been attributed to decreased water availability and increased soil temperature fluctuations observed after surface litter is removed (Evans and Young 1970;Adair et al 2008). …”
Section: Introductionmentioning
confidence: 99%
“…Following burning with herbicides can increase control duration; however, it is unclear exactly why this occurs. Studies have reported 4 that removing surface litter mechanically or through burning decreases seedling survival (Evans and Young 1970;Adair et al 2008), but other studies have postulated that reducing surface litter increases herbicide efficacy by decreasing the amount of herbicide bound to litter (Washburn et al 1999;DiTomaso et al 2006). Despite much speculation, no quantitative studies have been conducted examining how surface litter interacts with herbicides used to control downy brome.…”
Section: Introductionmentioning
confidence: 99%